Mapping The Field of Islamic Mutual Finance in Indonesia - Rizal Ma’ruf Amidy Siregar; Utari Evy Cahyani; Dia Purnama Sari (Universitas Islam Negeri (UIN) Walisongo Semarang, 2022)
AbstractPurpose - This study aims to find a comprehensive literature on Islamic mutual funds in Indonesia.Method - This study uses a qualitative approach with bibliometric analysis.Result - The results of the study identify leading academic authors, journals, and institutions related to Islamic mutual funds in Indonesia. Several popular topics and keywords for the theme of Islamic mutual funds in Indonesia have the potential to be studied further, especially related to the behavior of Islamic mutual fund investors in Indonesia.Implication - The importance of investor behavior for the development of the Islamic mutual fund industry in Indonesia.Originality - This study uses 101 publications indexed in the Dimensions database from 2006 to 2022. The keywords used in the data search are “Islamic mutual funds” AND “Indonesia”